Gas chromatography using ice-coated fused silica columns: study of adsorption of sulfur dioxide on water ice - Langenberg, Stefan; Schurath, Ulrich (Atmospheric chemistry and physics, 2018)
The well established technique of gas chromatography is used to investigate interactions of sulfur dioxide with a crystalline ice film in a fused silica wide bore column. Peak shape analysis of SO2 chromatograms measured in the temperature range 205-265 K is applied to extract parameters describing a combination of three processes: (i) physisorption of SO2 at the surface, (ii) dissociative reaction with water and (iii) slow uptake into bulk ice. Process (ii) is described by a dissociative Langmuir isotherm. The pertinent monolayer saturation capacity is found to increase with temperature. The impact of process (iii) on SO2 peak retention time is found to be negligible under our experimental conditions. By analyzing binary chromatograms of hydrophobic n-hexane and hydrophilic acetone, the premelt surface layer is investigated in the temperature range 221-263 K, possibly giving rise to irregular adsorption. Both temperature dependencies fit simple van't Hoff equations as expected for process (i), implying that irregular adsorption of acetone is negligible in the investigated temperature range. Adsorption enthalpies of −45 ± 5 and −23±2 kJ mol−1 are obtained for acetone and n-hexane. The motivation of our study was to assess the vertical displacement of SO2 and acetone in the wake of aircraft by adsorption on ice particles and their subsequent sedimentation. Our results suggest that this transport mechanism is negligible.
Gesehen am 24.02.2020